Failure of Laparoscopy to Relieve Ureteral Obstruction Secondary to Endometriosis - Hsing-Yu Chen; Ming-Chao Huang; Yu-Chung Hung; Yung-Hsuen Hsu (Elsevier, 2006)
Objective: To present a case of hydronephrosis and hydroureter secondary to pelvic endometriosis and to discuss the pitfalls in laparoscopic management. Case Report: A 37-year-old nulligravida woman had mild elevation of blood pressure for about 1 year without abdominal pain, dyspareunia, or dysmenorrhea. Renal ultrasound revealed left hydronephrosis and a 4-cm pelvic cyst. Intravenous pyelogram showed distal ureteral obstruction. An MRI with fat saturation disclosed a left ovarian endometrioma and a lesion in the uterosacral ligament causing periureteral compression. Laparoscopic findings included a dilated left ureter above the uterosacral ligament, left uterosacral ligament endometriosis with adhesions, and a 4-cm left ovarian endometrioma. Cystoureteroscopy showed external ureteral compression 2 cm above the ureteral orifice. A ureteral catheter was placed. The left endometrioma was enucleated and ureterolysis was performed. The latter procedure had to be discontinued because of bleeding from descending uterine vessels. The ureteral catheter was removed 2 months later and her blood pressure gradually returned to normal. However, after 1 year, she was found to have recurrent hydronephrosis and underwent segmental resection of the distal ureter and reconstruction by end-to-end reanastomosis. Conclusion: In women of reproductive age, hydronephrosis and hypertension may be the only symptoms of endometriosis. While laparoscopic treatment is useful in endometriosis, it may fail in the presence of chronic inflammation and severe fibrosis.